A rare cause of postpartum acute hyponatremia. (15th March 2019) - Rahmani Tzvi-Ran, Ilan; Olchowski, Judith; Fraenkel, Merav; Bashiri, Asher; Barski, Leonid
Summary: A previously healthy 24-year-old female underwent an emergent caesarean section without a major bleeding described. During the first post-operative days (POD) she complained of fatigue, headache and a failure to lactate with no specific and conclusive findings on head CT. On the following days, fever rose with a suspicion of an obstetric surgery-related infection, again with no evidence to support the diagnosis. On POD5 a new-onset hyponatremia was documented. The urine analysis suggested SIADH, and following a treatment failure, further investigation was performed and demonstrated both central hypothyroidism and adrenal insufficiency. The patient was immediately treated with hydrocortisone followed by levothyroxine with a rapid resolution of symptoms and hyponatremia. Further laboratory investigation demonstrated anterior hypopituitarism. The main differential diagnosis was Sheehan's syndrome vs lymphocytic hypophysitis. Brain MRI was performed as soon as it was available and findings consistent with Sheehan's syndrome confirmed the diagnosis. Lifelong hormonal replacement therapy was initiated. Further complaints on polyuria and polydipsia have led to a water deprivation testing and the diagnosis of partial central insipidus and appropriate treatment with DDAVP. Learning points: Sheehan's syndrome can occur, though rarely, without an obvious major post-partum hemorrhage. The syndrome may resemble lymphocytic hypophysitis clinically and imaging studies may be crucial in order to differentiate both conditions. Hypopituitarism presentation may be variable and depends on the specific hormone deficit. Euvolemic hyponatremia workup must include thyroid function test and 08:00 AM cortisol levels.